Thermodynamically stable polymorphs of nitrogen-rich carbon nitrides: a C3N5study - Ghasemi, S. Alireza; Mirhosseini, Hossein; Kühne, Thomas D. (Physical Chemistry Chemical Physics, 2021)
We have carried out an extensive search for stable polymorphs of carbon nitride with C3N5stoichiometry using the minima hopping method. Contrary to the widely held opinion that stacked, planar, graphite-like structures are energetically the most stable carbon nitride polymorphs for various nitrogen contents, we find that this does not apply for nitrogen-rich materials owing to the high abundance of N-N bonds. In fact, our results disclose novel morphologies with moieties not previously considered for C3N5. We demonstrate that nitrogen-rich compounds crystallize in a large variety of different structures due to particular characteristics of their energy landscapes. The newly found low-energy structures of C3N5have band gaps within good agreement with the values measured in experimental studies.
CRIS-Team Scopus Importer:2023-03-20